The Impact of Relationship Marketing Strategy in Indonesia Retail Industries - Freddy Pandapotan Simbolon (Bina Nusantara University, 2016)
This research aimed to examine the impact of relationship marketing strategy on customer loyalty in Indonesia’s retail industries. A questionnaire derived from previous studies and the relevant literature was completed by 182 retail customers in Jakarta. Multiple regression analysis assessed the impact on customer loyalty of four key constructs of relationship marketing (trust, commitment, communication, and conflict handling). The two variables (trust and commitment) had a significant effect and predicted a good proportion of the variance in customer loyalty. Moreover, they were significantly related to one another. The relationships investigated in this study deserved further research. Since the data analyzed were collected from one sector of the service industry in one region, more studies were required before general conclusions can be drawn. It is reasonable to conclude, on this evidence, that customer loyalty can be created, reinforced, and retained by marketing plans aimed at building trust, demonstrating a commitment to service, communicating with customers in a timely, reliable and proactive fashion, and handling conflict efficiently, reinforces and refines the body of knowledge relating to customer loyalty in service industries.